2020
DOI: 10.15252/embr.202050718
|View full text |Cite
|
Sign up to set email alerts
|

Non‐canonical ATM / MRN activities temporally define the senescence secretory program

Abstract: Senescent cells display senescence-associated (SA) phenotypic programs such as stable proliferation arrest (SAPA) and a secretory phenotype (SASP). Senescence-inducing persistent DNA doublestrand breaks (pDSBs) cause an immediate DNA damage response (DDR) and SAPA, but the SASP requires days to develop. Here, we show that following the immediate canonical DDR, a delayed chromatin accumulation of the ATM and MRN complexes coincides with the expression of SASP factors. Importantly, histone deacetylase inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 86 publications
(152 reference statements)
1
16
0
Order By: Relevance
“…Regarding the effect of SAHA treatment on SASP factors expression, SAHA treatment induced an increase in the expression of IL-6, IL-8 (CXCL8), MMP-1 , MMP-3 , IL-1β and Gro-α (CXCL1) at the mRNA level, whatever the dose and the duration of treatment ( Figure 2H ). Moreover, the secretion of IL-6 and IL-8 significantly increased from 24 hours for IL-6, and from 48 hours for IL-8 ( Figure 2I ), confirming a rapid effect of SAHA on SASP induction, as recently reported following the treatment of HDFs with sodium butyrate (NaB) and trichostatin A (TSA), two other HDACi [ 15 ].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Regarding the effect of SAHA treatment on SASP factors expression, SAHA treatment induced an increase in the expression of IL-6, IL-8 (CXCL8), MMP-1 , MMP-3 , IL-1β and Gro-α (CXCL1) at the mRNA level, whatever the dose and the duration of treatment ( Figure 2H ). Moreover, the secretion of IL-6 and IL-8 significantly increased from 24 hours for IL-6, and from 48 hours for IL-8 ( Figure 2I ), confirming a rapid effect of SAHA on SASP induction, as recently reported following the treatment of HDFs with sodium butyrate (NaB) and trichostatin A (TSA), two other HDACi [ 15 ].…”
Section: Resultssupporting
confidence: 84%
“…Moreover, it has been reported that normal immortalized human fibroblasts treated with NaB expressed a SASP via the activation of a non-canonical DDR pathway independently of the ATM kinase activity. This data highlights the fact that epigenetic changes associated to chromatin remodeling are involved in the establishment of the senescent phenotype including the SASP [ 11 , 15 ]. However, little is known about the changes in HDACs expression during senescence of normal cells and about the contribution of individual HDACs in the onset of senescence.…”
Section: Introductionmentioning
confidence: 92%
“…In part because of its ability to modify the environment and impact the behavior of other cells, the SASP is tightly regulated at multiple levels. Transcriptionally, various factors (C/EBPβ and NF-κβ) [ 9 , 10 ], upstream regulators (p38, MAPK, GAT4A, p53, or ATM) [ 5 , 50 , 51 , 52 , 53 ] and non-coding RNAs (miRNAs, lncRNAs and circRNAs) [ 54 ] have been described to regulate SASP expression. Additionally, mTORC1-mediated translational regulation of MAPKAPK2 and IL1A has been shown to impact several SASP factors [ 55 , 56 ].…”
Section: Role Of Sasp In Senescence and Cancermentioning
confidence: 99%
“…For instance, reduced Ki67 and elevated p16INK4a and p21 protein expression are common to quiescent and senescent cells (for a recent review see [ 5 ]) and quiescent neuronal stem cells, NSCs, in the subventricular zone have enlarged lysosome compared to activated NSCs [ 6 ]. Cell senescence is also characterized by the secretion of specific growth factors and cytokines, collectively defined as the senescence-associated secretory phenotype, SASP, which is induced as a delayed response to the pro-senescence stimuli [ 7 , 8 ]. Via autocrine and paracrine mechanisms, the SASP contributes to stabilize the senescent phenotype that normally becomes irreversible even after cessation of the senescence-inducing stimuli [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…DDR appears to be necessary for senescence induction, but other pathways contribute to the acquisition of a mature senescent phenotype. For instance, a non-canonical DDR, which requires the ATM kinase but not its enzymatic activity, is required for the recruitment of NF-kB on the promoter of SASP genes and the delayed expression of a mature SASP [ 7 ]. About twenty years ago, chemotherapeutic drugs and X-rays irradiation used for cancer treatment were shown to induce cellular senescence in several human tumor cell lines [ 21 ] and in vivo [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%